The effect of transformational leadership on organizational performance through the mediating role of organizational culture in higher education institutions in Iraq - Waham, Mohammed Ahmed (Tanjong Malim, 2022)
The effect of transformational leadership on organizational performance through the mediating role of organizational culture in higher education institutions in Iraq by Waham, Mohammed Ahmed